Faktor-Faktor Yang Mempengaruhi Terjadinya Baby Blues Pada Ibu Postpartum - Wahyuni, Sri; Yogi, Ruth; Irianda, Andi Irfa (Indonesian Journal Publisher, 2025)
Background: Baby blues is a condition of temporary emotional lability that usually occurs on the first day to two weeks after delivery, Mothers who experience baby blues will experience mood swings, feel sad, anxious, often cry, loss of appetite, and difficulty sleeping (insomnia), Baby blues can be categorized as a mild mental disorder syndrome. Objective: This study aims to determine the factors that influence the occurrence of Baby Blues in postpartum mothers at the Timika Health Center. Method: This study is an observational study with a cross-sectional study design, to study the factors that influence Baby Blues in Postpartum mothers. The sampling technique with a total sampling of 30 respondents. Results: the results of this study explain that there is a significant relationship between childbirth readiness with a p-value = 0.000, pregnancy status with a p-value = 0.004 and social support with a p-value = 0.000 with the occurrence of baby blues in postpartum mothers at the Timika Health Center. Conclusion: baby blues can be influenced by a lack of social support from those closest to you. Social support is an important coping strategy for mothers experiencing postpartum stress and functions as a preventive strategy to reduce stress.